Virtual instrumentation applied in the development of a transformer test bench (Research, Society and Development, 2021)
The transformer is important in several areas of electrical engineering, so in order to verify the efficiency of the equipment, tests are performed. Short-circuit and open-circuit tests are relevant because they allow the determination of quantities that represents the real transformers model. The objective of this work was to develop an automated short-circuit and open circuit testing system for low voltage single-phase transformers using virtual instrumentation through LabVIEW, reducing operator interference and, consequently, obtaining more accurate results, in less time and with greater confidence. Therefore, a bibliography study, the determination of current and voltage sensors, the construction of the test bench, creation of the software in LabVIEW, calibration, testing, application, analysis and presentation of results were carried out. The system presented accurate results, with low quality error, which allowed the operator, once the arrangement of tests has been assembled, the unnecessary use of instruments during the tests.